2000
DOI: 10.1136/vr.147.4.110
|View full text |Cite
|
Sign up to set email alerts
|

Possible distinction between sole ulcers and heel ulcers as a cause of bovine lameness

Abstract: O\lS Iautliotsxcoxsidetthat a sole Lolcciis for-ied xxwhen cxcxsx pICiSII-C (u il the c(Iiilu-letIads to hrFtiSing if tlhe dcI-Imal fpapil-laC o(f the xsti tu ll crtmi atix urn1 xxith SL xbS(x cunt dixi OptiOIn of h1orII f-o0'il matiOnl (TOLxSxainit Raxven 1 983a, Blowxc 1993, C(ollick 199T7, Oxsxent atid I ischer 1998). 1'ltc Stt'atlUIml gyeiIli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…It has been theorized that subclinical laminitis weakens the suspensory system and thereby predisposes the cow to SU and WLD (Thoefner et al, 2004), although evidence supporting this theory is limited (Danscher et al, 2010). New bone development on the third phalanx (Rusterholz, 1920;Blowey et al, 2000;Lischer et al, 2002) is associated with increasing age (Tsuka et al, 2012;Newsome et al, 2016) and is thought to contribute to a higher incidence of ulceration (Rusterholz, 1920;Tsuka et al, 2012). Because foot and leg conformation influences weight distribution within and between claws, the foot and leg conformation traits are thought to be correlated with SU + WLD susceptibility, although stronger evidence is needed to support the low to moderate phenotypic (Capion et al, 2008;Pérez-Cabal and Charfeddine, 2016) and genetic (Chapinal et al, 2013) correlations that were previously observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been theorized that subclinical laminitis weakens the suspensory system and thereby predisposes the cow to SU and WLD (Thoefner et al, 2004), although evidence supporting this theory is limited (Danscher et al, 2010). New bone development on the third phalanx (Rusterholz, 1920;Blowey et al, 2000;Lischer et al, 2002) is associated with increasing age (Tsuka et al, 2012;Newsome et al, 2016) and is thought to contribute to a higher incidence of ulceration (Rusterholz, 1920;Tsuka et al, 2012). Because foot and leg conformation influences weight distribution within and between claws, the foot and leg conformation traits are thought to be correlated with SU + WLD susceptibility, although stronger evidence is needed to support the low to moderate phenotypic (Capion et al, 2008;Pérez-Cabal and Charfeddine, 2016) and genetic (Chapinal et al, 2013) correlations that were previously observed.…”
Section: Discussionmentioning
confidence: 99%
“…Compression damage of the corium occurs readily in these zones because the distal phalanx drops both in the downward direction and toward the axial wall of the hoof (Maclean, 1970;Lischer et al, 2002; van Amstel and Shearer, 2006). These zones are directly beneath the tuberculum flexorium of the distal phalanx, the ventral surface of the distal phalanx in the region of the insertion of the deep digital flexor tendon (Blowey et al, 2000;Desrochers and Anderson, 2001). The tuberculum flexorium possesses a natural downward protruding structure and is anatomically involved in the pathogenesis of sole ulcer (Desrochers and Anderson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative evaluation of bone development of the distal phalanx of the cow hind limb using computed tomography T. Tsuka ,* 1 K. Ooshita, † A. Sugiyama,* T. Osaki,* Y. Okamoto,* S. Minami,* and T. Imagawa * Therefore, exostosis of the distal phalanx is believed to be an exacerbating factor for ulcer formation (Blowey et al, 2000;Lischer et al, 2002). Mechanical damage of the corium layer due to the exostosis in the tuberculum flexorium is evident by sole hemorrhage and necrosis of the corium (Blowey et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Heel ulcers have been described as being related to but distinct from sole ulcers; they occur more caudally than the typical sole ulcer site, appear more prevalent in older animals, and recover poorly in comparison (Toussaint-Raven, 1985;Blowey et al, 2000;Haslam and Roberts, 2011). We observed extensive bone development caudal to the distal phalanx, which extended up to 28.2 mm; the caudal limit of large bone development corresponded with the heel ulcer site.…”
Section: Discussionmentioning
confidence: 99%
“…Bone developments appear on and around the flexor tuberosity with age (Tsuka et al, 2012) and have been termed "exostosis" (Maclean, 1970;Blowey et al, 2000;Lischer et al, 2002), indicating growth of new bone from the surface of a bone, or "enthesopathy" (Tsuka et al, 2012), indicating the inclusion of an enthesis (the insertion of a tendon or ligament onto bone). The new bone development may be an exacerbating factor for ulceration (Rusterholz, 1920;Maclean, 1970;Tsuka et al, 2012), and appears greater in cows with sole ulcers at slaughter (Tsuka et al, 2012), yet a link between lifetime history of lameness and lesions has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%